2011
DOI: 10.1038/pr.2011.371
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging (MRI) Findings in Epileptic Children and its Relation with Clinical and Demographic Findings

Abstract: Introduction:Epilepsy is an important disease with a cumulative incidence of 3% all over the life and more than half of them are started from childhood. In this study we surveyed MRI findings in epileptic children and its relation with clinical and demographic findings in order to find better diagnostic and treatment modalities for these children in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 0 publications
5
15
1
Order By: Relevance
“…Cumulative incidence of epilepsy is 3 % all over the life and more than half of them are started since childhood period. 2 Epilepsy affects 0.5-1% of children and it is one of the most common chronic neurologic disorder among children. Incidence is higher in underdeveloped countries, when compared with developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative incidence of epilepsy is 3 % all over the life and more than half of them are started since childhood period. 2 Epilepsy affects 0.5-1% of children and it is one of the most common chronic neurologic disorder among children. Incidence is higher in underdeveloped countries, when compared with developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study revealed abnormal MRI of brain in 28.50% of children. The abnormalities included brain atrophy (10%), leukoencephalopathy (8%), benign cysts (5%), brain tumors (4%) and vascular abnormalities (1.50%) [14]. In the present study, the MRI abnormalities included atrophy in 58 (40.27%); signal alterations in 61 (42.36%) and ventriculomegaly in 29 (20.13%) patients.…”
Section: Discussionmentioning
confidence: 44%
“…(5,21) Amirsalari et al in their cross-sectional study of 200 Iranian epileptic children reported predominance of focal seizures than generalised seizures. (26) Focal seizures constituted 79% of the seizure type in the study by Wongladarom et al (24) Epileptic syndromes were observed in only 10 patients (12.5%), whereas Dura Trave et al reported high prevalence of the same. (27) Two cases, each of BECTS, CAE, Dravet Syndrome and four cases of Lennox-Gastaut Syndrome were present with normal MRI in three cases.…”
Section: Discussionmentioning
confidence: 90%
“…Amirsalari et al reported positive family history in 56.5% and this series had only in 20%. (26) 43% had a history of status epilepticus, either during presentation or later. Study by Berg et al in 613 American children showed status epilepticus in as little as 9.1%.…”
Section: Discussionmentioning
confidence: 99%